Association study of Retinoic Acid Related Orphan Receptor A (RORA) gene and risk of prostate disorders - Taheri, Mohammad; Noroozi, Rezvan; Dehghan, Alireza; Atri Roozbahani, Golnaz; Musavi, Mehrnoosh; Omrani, Mir Davood; Ghafouri-Fard, Soudeh (Urology Journal, 2019)
Purpose: Prostate cancer (PCa) and benign prostate hyperplasia (BPH) are two prevalent disorders among men with considerable mortality and morbidity. Several association studies have been conducted in different populations to find genetic loci linked with these disorders. Retinoic acid-receptor-related orphan receptor alpha (RORA) codes for a transcription factor which regulates expression of several cancer-related genes. Besides, RORA has been shown to be down-regulated in PCa tissues and cell lines. Materials and Methods: In the present study we evaluated genotype and allele frequencies of rs11639084 and rs4774388 variants within RORA gene in PCa and BPH patients compared with healthy subjects. Results: The rs11639084 and rs4774388 alleles were not different between PCa and normal groups 95% CI: 0.52-1.24, OR = 1.04, P = .34; 95% CI: 0.48-1.33, OR = .79, P = .39 respectively. Moreover, we did not detect any significant difference in allele, genotype or haplotype frequencies of these SNPs between the other study groups. Conclusion: The mentioned RORA variants are possibly not involved in the pathogenesis of PCa and BPH. Future studies are needed to assess the associations between other variant within this gene and PCa risk to suggest a putative mechanism for involvement of RORA in PCa.